PENGARUH MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI BANGUNHARJO BANTUL YOGYAKARTA - Ayuningtyas, Ardita; Hidayati, Hidayati (Universitas Sarjanawiyata Tamansiswa, 2021)
Descriptively, this research aims to determine the tendency of science learning outcomes of fourth-grade students at SD N Bangunharjo whose learning uses interactive multimedia and image media. Comparatively, this research aims to find out the differences in science learning outcomes of Grade IV students of SD N Bangunharjo between learning using interactive multimedia and image media. The type of this research is a quasi-experiment. The Data collection techniques were documentation to retrieve students' initial ability data and test technique to retrieve test data. Descriptive data analysis techniques using ideal normal curves and comparatively using t-test. The analysis prerequisite tests include the distribution normality test and the variance homogeneity test. The Descriptive research result indicates that the tendency of science learning outcomes that using interactive multimedia are included in the highest category and those using image media are included in the high category. Comparatively, there is a significant difference in science learning outcomes between learning using interactive multimedia and image media, with t = 2.34 and p = 0.023. The average of science learning outcomes with interactive multimedia is higher than image media. Thus, it can be concluded that there is an influence of interactive multimedia on the learning outcomes of fourth-grade students of SD N Bangunharjo.